2021
DOI: 10.3390/v13020232
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2-Inactivating Activity of Hydroxytyrosol-Rich Aqueous Olive Pulp Extract (HIDROX®) and Its Use as a Virucidal Cream for Topical Application

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread globally. Although measures to control SARS-CoV-2, namely, vaccination, medication, and chemical disinfectants are being investigated, there is an increase in the demand for auxiliary antiviral approaches using natural compounds. Here we have focused on hydroxytyrosol (HT)-rich aqueous olive pulp extract (HIDROX®) and evaluated its SARS-CoV-2-inactivating activity in vitro. We showed that the HIDROX solution exhibits time- and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…Lately, it has been shown that oleuropein and HT in extracts obtained from leaves or OWW, respectively, display antiviral activities against the SARS-COV2, possibly by inducing structural changes of the virus [26][27]. Hydrogel or cream enriched with HT has been proposed as an antiviral hand cream [26].…”
Section: Exploitation and Alternative Use Of Olive Oil Byproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, it has been shown that oleuropein and HT in extracts obtained from leaves or OWW, respectively, display antiviral activities against the SARS-COV2, possibly by inducing structural changes of the virus [26][27]. Hydrogel or cream enriched with HT has been proposed as an antiviral hand cream [26].…”
Section: Exploitation and Alternative Use Of Olive Oil Byproductsmentioning
confidence: 99%
“…Lately, it has been shown that oleuropein and HT in extracts obtained from leaves or OWW, respectively, display antiviral activities against the SARS-COV2, possibly by inducing structural changes of the virus [26][27]. Hydrogel or cream enriched with HT has been proposed as an antiviral hand cream [26]. On another hand, it has been proposed that phytosomal formulation containing luteolin (in olive pomace oil) may mitigate some of the symptoms observed in long-COVID patients [28].…”
Section: Exploitation and Alternative Use Of Olive Oil Byproductsmentioning
confidence: 99%
“…As mitochondria-mediated aging is associated with dysregulated metabolism and requires novel therapeutic modalities viz., mitochondrial anti-oxidants and anti-inflammatory molecules are likely to correct these dysregulated metabolic and physiological processes before the administration of vaccines against SARS-CoV-2-induced neuropathology [123]. "Hydroxytyrosol (HT)-rich aqueous olive pulp extract (HIDROX®)" has been reported to mitigate SARS-CoV-2-induced pathophysiology by inducing potent virucidal activity [124]. Hydroxytyrosol (HT) and oleuropein aglycone (OLE) are two potential molecules reported being beneficial to mitigate the pathophysiology of neurodegeneration [124].…”
Section: Sars-cov-2 and A Robust Mitochondrial System And Immune-competency Rely On Hormesismentioning
confidence: 99%
“…"Hydroxytyrosol (HT)-rich aqueous olive pulp extract (HIDROX®)" has been reported to mitigate SARS-CoV-2-induced pathophysiology by inducing potent virucidal activity [124]. Hydroxytyrosol (HT) and oleuropein aglycone (OLE) are two potential molecules reported being beneficial to mitigate the pathophysiology of neurodegeneration [124]. Hormesis and anti-oxidant nature, which enhances the activity of proteasome and phase II detoxifying enzymes, are potential mechanisms of action by which these pharmacological molecules work against SARS-CoV-2-induced neuropathophysiology [125,126].…”
Section: Sars-cov-2 and A Robust Mitochondrial System And Immune-competency Rely On Hormesismentioning
confidence: 99%
“…Other antiviral mechanisms proposed by some authors against SARS-CoV-2 observed in antioxidant compounds are: (a) inhibition of the viral replication (i.e., curcumin and resveratrol) [ 239 , 240 ], (b) blockage of the inflammatory response (i.e., resveratrol, curcumin, naringenin, and N-acetil cysteine) [ 207 , 239 , 240 , 241 ], (c) inhibition of SARS-CoV-2 fusion/entry by interaction with SARS-CoV-2:ACE-2 interface (luteolin and dithymoquinone) [ 242 , 243 ], (d) as radical scavengers (i.e., methide quinone celastrol as superoxide radical scavenger or hydrogen as hydroxyl radical scavenger) [ 214 , 244 ], (e) inhibition of ACE activity (N-acetyl cysteine) [ 245 ], (f) modulation of endoplasmic reticulum stress (andrographolide and melatonin) [ 246 ], (g) activation of Nrf2 pathway (antioxidant mixture PB125 ® ) [ 247 ], (h) antithromboembolics (hesperidin and diosmin mixture) [ 248 ], and (i) inducing aggregation of SARS-CoV-2 spike proteins and disruption of the viral genome (hydroxytyrosol) [ 249 ]. Figure 2 shows the mechanisms of antioxidants compounds that could prevent neuronal damage in patients with COVID-19…”
Section: Mechanisms Of Antioxidants Compounds Against Sars-cov-2 In Covid-19mentioning
confidence: 99%